CONSUMERS PERCEPTION OF COMMUNICATION STRATEGIES OF SUSTAINABLE FASHION COMPANIES - Santoro, Vitória Didoné; Felith de Medeiros , Janine; Kolling , Camila (Brazilian Creative Industries Journal, 2025)
Fashion is one of the sectors responsible for generating negative socio-environmental impacts, leading the public to become aware of sustainable aspects when consuming. An existing challenge involves understanding how fashion companies must communicate their sustainable position. Therefore, this article aims to present an overview of the associations that the public makes from different communications on sustainability. Specifically, we seek to understand the role of rational and emotional persuasion in communication, especially in the advertising of responsible brands. For this, we conducted an exploratory research with young people from 18 to 24 years old. The data collection approach includes the analysis of the sample's perceptions after exposure to videos and publications on social media of two brands recognized as environmentally responsible in the fashion sector. Our results show that emotional persuasion is more effective in generating identification and representation. The subjective elements evidenced in brand communication that uses emotional appeal tend to direct purchase intention more than attributes, benefits, and advantages described in brand communication that uses rational appeal. The study advances discussions on sustainable transition in the fashion industry by exploring more effective communication strategies to position brands and encourage pro-environmental purchasing behavior in this sector.